Safety Profile for Microneedling: A Systematic Review. Issue 9 (September 2021) - Chu, Sherman; Foulad, Delila P.; Atanaskova Mesinkovska, Natasha
Abstract : BACKGROUND: Microneedling is a minimally invasive procedure that stimulates collagen and elastin proliferation. It is used in the treatment of various skin pathologies, that is, scarring, photodamage, and hair loss; however, its safety profile has yet to be comprehensively reviewed. OBJECTIVE: This review will discuss the reported side effects of microneedling in the current literature and delineate factors that increase the risk of complications. MATERIALS AND METHODS: A literature search in August 2019 was conducted using the PubMed database to identify studies reporting adverse events (AEs) after microneedling therapy. RESULTS: Eighty-five articles were included in this systematic review. The most common reported AEs are transient procedural events that are expected postprocedure lasting up to 7 days, such as transient erythema/edema and pain, postinflammatory hyperpigmentation (PIH), dry skin/exfoliation, lymphadenopathy, and irritant contact dermatitis. Persistent serious adverse effects included PIH, tram-track scarring, and granulomatous reactions. Factors that increase the risk of events are active infections, darker skin, and metal allergies. CONCLUSION: Microneedling is a relatively safe therapy. Most reported AEs are minimal, resolving quickly and spontaneously. Caution should be taken in patients with active infection, darker skin types, metal allergies, and when used in conjunction with products not approved for intradermal use. Abstract : Supplemental Digital Content is Available in the Text.